2021
DOI: 10.1016/j.intimp.2021.107398
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide an immunomodulator with antineoplastic and antiviral potentials but drug-induced liver injury: A comprehensive review

Abstract: Leflunomide (LF) represents the prototype member of dihydroorotate dehydrogenase (DHODH) enzyme inhibitors. DHODH is a mitochondrial inner membrane enzyme responsible for catalytic conversion of dihydroorotate into orotate, a rate-limiting step in the de novo synthesis of the pyrimidine nucleotides. LF produces cellular depletion of pyrimidine nucleotides required for cell growth and proliferation. Based on the affected cells the outcome can be attainable as immunosuppression, antiprolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 139 publications
(105 reference statements)
0
27
0
Order By: Relevance
“…DHODH inhibitors (DHODHi) have been used to treat malignant tumors, autoimmune diseases, viral or bacterial infections, parasitic diseases, and other diseases [ 23 , 31 , 33 , 34 , 35 ]. DHODHi inhibit viral infection by three mechanisms: (1) inhibiting viral replication (pathway 1 in Figure 2 ), (2) promoting interferon-stimulated genes (ISGs) expression (pathway 2 in Figure 2 ), and (3) regulating inflammation (pathway 3 in Figure 2 ).…”
Section: The Essential Role Of Dhodh In the De Novo ...mentioning
confidence: 99%
“…DHODH inhibitors (DHODHi) have been used to treat malignant tumors, autoimmune diseases, viral or bacterial infections, parasitic diseases, and other diseases [ 23 , 31 , 33 , 34 , 35 ]. DHODHi inhibit viral infection by three mechanisms: (1) inhibiting viral replication (pathway 1 in Figure 2 ), (2) promoting interferon-stimulated genes (ISGs) expression (pathway 2 in Figure 2 ), and (3) regulating inflammation (pathway 3 in Figure 2 ).…”
Section: The Essential Role Of Dhodh In the De Novo ...mentioning
confidence: 99%
“…Exogenous uridine (100 μM) supplementation significantly decreased the proliferation inhibitory rate to 3.3, 6.2, 17.1, and 21.3%, respectively, suggesting that exogenous uridine predominantly rescued proliferation inhibition induced by compound 13t . Furthermore, previous studies revealed that teriflunomide also exhibited inhibitory activities against several human protein kinases, such as EGFR, JAK1, and JAK3. Therefore, we evaluated the inhibitory activities of 13t (10 μM) against 98 human protein kinases that are commonly activated in human malignancies including EGFR, JAK1, and JAK3. The results showed that 13t at a high concentration of 10 μM only affected the protein kinases activity very slightly with most of the inhibitory rate lower than 30% (Table S1), suggesting that 13t did not affect the kinases activity.…”
Section: Resultsmentioning
confidence: 99%
“…Lef is a malononitrile derivative that inhibits dihydroorotate dehydrogenase and several protein tyrosine kinases [ 43 , 44 ]. Although Lef is an immunomodulatory agent used to treat rheumatoid arthritis [ 45 ], there have been no studies on the effects of Lef on osteoblastic differentiation. Malviya et al reported that 15 µM Lef inhibited the proliferation of primary human osteoblasts [ 46 ].…”
Section: Discussionmentioning
confidence: 99%